An introduction to ICD code development for pediatric neurology - Monika J. Baker; Joshua L. Bonkowsky (Wiley, 2023)
Abstract Objective Querying large data sets in the United States is challenging due to limitations of International Classification of Diseases 10th edition Clinical Modification (ICD‐10‐CM) codes. ICD codes were developed for tracking mortality and for billing purposes but are also the most widely used data structure to represent clinically significant and distinct disorders. We report an approach for developing new ICD codes based on our work creating new codes for leukodystrophies. Methods Important steps in ICD‐10‐CM code development include working with the ICD‐10‐CM Coordination and Maintenance Committee, a subset of the National Center of Health Statistics (NCHS); working to ensure the code has the best placement and is appropriate for submission; presenting the code and accompanying proposal (rationale) at a Coordination and Maintenance Committee Meeting; and requesting letters of support and addressing concerns raised by various groups. Results We describe the historical development of ICD codes as well as their current hierarchical structure. Important features for successful code development included consulting future ICD‐11‐CM code structure; determining which codes are most important to the community; having a multidisciplinary approach; and obtaining organizational and institutional support. Conclusion Focusing on the clinical importance of leukodystrophy codes was important for their approval. Although challenging, there is a route for new code development, and we were ultimately successful in obtaining approval for 10 new leukodystrophy ICD‐10‐CM codes. Understanding ICD codes and their structure, considering their usage for clinical and research work, and appreciating how new codes can be developed is important for the pediatric neurology community.